Chefspyramidens komplexitet : En studie om områdeschefsbefattningen vid Luleå Kommuns Socialförvaltning - Nordgren, Andreas (2014)
The purpose of this study was to examine the factor that resulted in the social service administration in Luleå instituted a new position, a middle manager between the unit manager and operations manager which is the area manager. Each level of manger; unit manager, area manager, director of operations and associated union party in the study, among other things, carrying their perspective on what is included in the new managers mission. The purpose of this is to see how the new area manager assignments are interpreted between the manager level and union party. The experience are also related to crystallize what the area manager meant for the administration, thereto which advantages and disadvantages that could be inferred based on reports from director of operation, area managers, unit managers and union representatives.There are a number of factors that resulted in a new level of manager in the social services administration in Luleå. In a review in 2009, it was clarified that the operational issues were at risk of operations manager whose mission also had a strategic aspect that was overlooked. The operation manager had also signaled that they didn´t had the stamina to be there for the unit managers while National Board of Health signaled the need for a near leadership.The new manager level has meant that the administration can work more consistently which is done by that the area manager follows up and look over for example, the head of unit scorecards work. Furthermore, the administration considerably gets greater insight into their regions since the area manager is reviewing that the data are recorded. Furthermore by a closer leadership the unit manager are given the opportunity to get feedback on their own work. Area manager is a quality improvement to social services regarding benefit to customers and the social service transparency towards citizens. Disadvantages based on the area manager genesis are that the unit manager perceives themselves controlled. This is based on a regular review of the unit ...